Atomic mixing behavior of Co/Al(001) vs. Al/fcc-Co(001): Molecular dynamics simulation - Kim, SP; Lee, SC; Lee, KR; Chung, YC (SPRINGER, 2004)
Using molecular dynamics simulations, we investigated the interface structures and the growth behaviors of nano-scale Al/Co/Al multilayers. For Co on Al(001), interface mixing occurred irrespective of the incident energy (K-i). Interestingly, increasing the incident energy increased the thickness of the mixing layers and decreased the roughness of the Co surface. In the case of Al on Co(001), in contrast to the case of Co/Al, interface mixing could not be found, especially for low incident energy. From these investigations, an optimized deposition technique is proposed that improves the quality of the interface/surface of the deposited thin film by controlling the incident adatom energies.
Keywords: MAGNETIC-PROPERTIES; EPITAXIAL-GROWTH; FILM GROWTH; AL SURFACE; CO; SANDWICHES; AU; AG(110); METALS